Distribution of Organic-Tempered Pottery in Southeast Europe and the Near East: A Complex Picture. The Case of Northern Greece - Papadakou Trisevgeni (De Gruyter, 2021)
Organic-tempered pottery is considered characteristic for the early pottery assemblages in most parts of Southwest Asia and Southeast Europe. The aim of the present paper is to explore: (a) the chronological consistency of this practice, i.e. is it always related to the early assemblages and how intensively was it employed by the various communities? and (b) is its use related to vessel type, surface treatment etc. and how does this change in time and space? In order to address these questions we explore the distribution patterns of this practice in this large geographical area, based on published information, since the appearance of pottery in the Near East until the early sixth millennium in Southeast Europe. Moreover, in the case of the Early Neolithic in Greece, new data is presented on the appearance and distribution of organic-tempered pottery within the assemblages of six newly studied sites in northern Greece, spanning the second half of the seventh millennium BC and the beginning of the sixth millennium BC. The emerging picture indicates that the cultural practice of organic tempering was available in all of this area for almost a millennium, although the significations may have not remained unaltered, and variably embraced by the various Neolithic communities. As such, this study offers insights into the complex process of neolithisation, and at the same time contextualizes the appearance of organic-tempering in northern Greece, which includes some of the earliest Neolithic sites in Europe.